Bile Duct Injury during Laparoscopic Cholecystectomy: Risk Factors, Mechanism and Prevention (Journal of Surgical Sciences, 2019)
Abstract not availableJournal of Surgical Sciences (2016) Vol. 20 (2) :35-36